Critical Examination of Halal Industry Policy In Indonesian - Moh Zaenal Muttaqin; Nurodin, Nurodin (al-Afkar, Journal For Islamic Studies, 2024)
The halal industry is a derivative of the sharia economic concept that has grown in Indonesia since the 1990s. Sharia economics is a value extracted from primary sources (the Koran and hadith) in Islam, and "halal" is a manifestation of that value. Muamalah jurisprudence defines sharia economics as economic activity that is free of usury, does not contain fraud, ambiguity, elements of compulsion and the most important thing is to guarantee the benefit of as many people as possible. The method of this article uses library research, namely a method of collecting data by understanding and studying theories from various literature related to research. From the analysis, it can be found that Indonesia is a country that has potential in developing the halal industry. This can be seen from several distinctive competencies possessed. Aspects that need to be encouraged in the halal industry in Indonesia are regulations, certification policies and facilities for MSMEs in running their businesses. Policies in the law need to be optimized and legality can be done quickly without complications. These conveniences will make it easier for people to develop all their potential.